Effect of position of donor units and alkyl groups on dye-sensitized solar cell device performance: indoline-aniline donor-based visible light active unsymmetrical squaraine dyes - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Om., 2024)
Indoline (In) and aniline (An) donor-based visible light active unsymmetrical squaraine (SQ) dyes were synthesized for dye-sensitized solar cells (DSSCs), where the position of An and In units was changed with respect to the anchoring group (carboxylic acid) to have In-SQ-An-CO2H and An-SQ-In-CO2H sensitizers, AS1-AS5. Linear or branched alkyl groups were functionalized with the N atom of either In or An units to control the aggregation of the dyes on TiO2. AS1-AS5 exhibit an isomeric pi-framework where the squaric acid unit is placed in the middle, where AS2 and AS5 dyes possess the anchoring group connected with the An donor, and AS1, AS3, and AS4 dyes having the anchoring group connected with the In donor. Hence, the conjugation between the middle squaric acid acceptor unit and the anchoring -CO2H group is short for AS2, AS5, and AK2 and longer for AS1, AS3, and AS4 dyes. AS dyes showed absorption between 501 and 535 nm with extinction coefficients of 1.46-1.61 x 10(5) M-1 cm(-1). Further, the isomeric pi-framework of An-SQ-In-CO2H and In-SQ-An-CO2H exhibited by means of changing the position of In and An units a bathochromic shift in the absorption properties of AS2 and AS5 compared to the AS1, AS3, and AS4 dyes. The DSSC device fabricated with the dyes contains short acceptor-anchoring group distance (AS2 and AS5) showed high photovoltaic performances compared to the dyes having longer distance (AS1, AS3, and AS4) with the iodolyte (I-/I-3(-)) electrolyte. DSSC device efficiencies of 5.49, 6.34, 6.16, and 5.57% have been achieved for AS1, AS2, AS3, and AS4 dyes, respectively; without chenodeoxycholic acid (CDCA), small changes have been observed in the device performance of the AS dyes with CDCA. Significant changes have been noted in the DSSC parameters (open-circuit voltage V-OC, short-circuit current J(SC), fill factor ff, and efficiency eta) for the AS5 dye while sensitized with CDCA and showed highest DSSC efficiency of 8.01% in the AS dye series. This study revealed the potential of shorter SQ acceptor-anchoring group distance over the longer one and the importance of alkyl groups on the overall DSSC device performance for the unsymmetrical squaraine dyes.

Effect of cyclization and alkyl group wrapping in visible-light-active unsymmetrical squaraine dyes for dye-sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Shivankar, Bhavana R.; Siby, Jesna; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2025)
A series of alkyl group-appended indoline- and carboxylic acid-functionalized indolenine-based visible-light-active unsymmetrical squaraine dyes, SQA7-10, were designed, synthesized, and utilized for the dye-sensitized solar cells device fabrication. The number of alkyl group has been increased systematically on the indoline moiety to control the self-assembly of dyes on TiO2 and to passivate the photoanode that helps in improving the open-circuit voltage (V-OC) by avoiding the charge recombination process. SQA7-10 dyes showed an absorption between lambda(max) 536-540 nm, with molar extinction coefficients of 1.62-2.13 x 10(5) M-1 cm(-1) in CH3CN. Further, ultraviolet-visible (UV-vis) studies on TiO2 indicated the formation of H-aggregated dyes (505-510 nm), which can be controlled by appending the alkyl groups. The energy levels of the highest occupied molecular orbital (HOMO) of these dyes are well aligned with the Nernst potentials of I-/I(3)(-)electrolyte and [Cu(tmby)(2)](+/2+) electrolytes with sufficient overpotentials required for the dye regeneration process. DSSC devices made with these dyes showed systematic enhancements of open-circuit voltage (V-OC) and device efficiency with respect to alkyl group incorporation for SQA7-10 with I-/I-3(-) electrolytes. All of the SQA dyes exhibited the device V-OC of more than 805 mV, where the introduction of alkyl groups systematically enhanced the V-OC in the order of SQA7 (805 mV) < SQA8 (829 mV) < SQA9 (843 mV) < SQA10 (862 mV) without any addition of CDCA. Within the SQA dye series, SQA10 dye has achieved the highest DSSC device efficiency of 7.52% (J(sc) of 11.16 mA/cm(2), V-oc of 862 mV, and ff of 78%) with I-/I-3(-) electrolyte, whereas use of [Cu(tmby)(2)](+/2+) redox shuttle with SQA10 showed enhanced V-oc (1080 mV) and device efficiency (8.35%). The IPCE profile for the device fabricated with SQA dyes showed good response at 480 and 560 nm, which indicates the photocurrent generation from the aggregated structures.
Keywords: aggregation of dyes; charge recombination; Dye-sensitized solar cells; indoline and indolenine donors; visible-light-activeunsymmetrical squaraine dye